Reddit as a Social Media Self-Management Tool for Inflammatory Bowel Disease: Qualitative Analysis - Tosin Adeyemi; Brian Gutermuth; Gal Hodish; Jeffrey Berinstein; Kira Newman; Sarah Hawley; Minal Patel; Peter Higgins; Ken Resnicow; Sarah Krein; Shirley Cohen-Mekelburg (Journal of Medical Internet Research)
Abstract BackgroundGiven the widespread discussion of inflammatory bowel disease (IBD)–related topics on social media, these platforms play an important role in increasing our understanding of the needs, preferences, and experiences of patients living with IBD. ObjectiveThis study aims to develop an in-depth understanding of Reddit (Reddit, Inc) social media discussions related to individuals’ experiences and perspectives living with and managing inflammatory bowel disease. MethodsWe identified threads on the r/IBD, r/Ulcerative Colitis, and r/CrohnsDisease subreddits between April 2022 and 2024 using a priori ResultsWe identified 659 posts comprising 207 (31.4%) original and 452 (68.6%) reply posts related to patients living with IBD. Findings highlighted that people use Reddit to seek knowledge, advice, empathy, and validation as well as to share experiences in five key areas related to: (1) symptoms as a major burden of patients living with IBD; (2) experiences with medications and concerns about treatment choices; (3) health care–related challenges; (4) dietary regimens and dietary guidance for handling symptoms and overall treatment; and (5) negative impact of IBD on mental health. ConclusionsUse of social media as an avenue for patients with IBD to gain knowledge, empathy, and support suggests that traditional clinical care does not fully address the needs of patients living with IBD as it relates to IBD knowledge, advice, empathy, validation, and sharing of experiences. While social media platforms can provide a platform for patients to share their experiences and build community, study findings also inform future efforts to address identified gaps in care, including the development of interventions to assist patients in managing their symptoms, diet, medications, health care, and mental health concerns.